Reducing substances in the blood of normal and alloxan treated fish - Moule, Margaret Laura (My University, 1962)
Blood sugar levels were determined in toadfish and catfish by the Folin reducing procedure and a specific enzymatic glucose procedure. The difference between the two values was considered to be the rest reduction (RR). After alloxan injection, the RR level increased greatly reaching a peak at one hour and then decreasing. The glucose level rose more slowly. An attempt was made to study these changes in blood by paper chromatography using silver nitrate to detect reducing compounds. In normal blood, glucose, an unidentified compound, and several other reducing compounds present in small amounts were separated. The large amount or RR present after alloxan could not be detected by silver nitrate. The significance of the results was discussed and future investigations were suggested.
Fish blood reducing substances
Keywords: blood sugar; toadfish; catfish; blood glucose; rest reduction; alloxan; paper chromatography